2017
DOI: 10.1111/1759-7714.12413
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of weekly intravenous nanoparticle albumin‐bound paclitaxel for non‐small cell lung cancer patients who have failed at least two prior systemic treatments

Abstract: BackgroundThe study was conducted to evaluate the efficacy and safety of weekly intravenous nanoparticle albumin‐bound paclitaxel (NAB‐paclitaxel) treatment in patients with advanced non‐small‐cell lung cancer (NSCLC) who have undergone multi‐line therapy, and to investigate the association of secreted protein acidic and rich in cysteine (SPARC) expression status with clinical outcome.MethodsSixty‐four patients who received NAB‐paclitaxel treatment (130 mg/m2 on days 1 and 8 of a 21 day cycle) as third line or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This is also consistent with the known safety profiles of nab-PTX and bevacizumab [21][22][23]30]. Using nab-PTX alone, the rates of grade 3-4 leukopenia, neutropenia, and anemia have been reported to be 5%-49%, 2%-69%, and 0%-32% [24,27,28,[37][38][39][40]. In a study of nab-PTX combined with carboplatin, neutropenia, thrombocytopenia, and anemia were observed in 28.0%, 12.0%, and 8.0% of the patients, respectively [41].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is also consistent with the known safety profiles of nab-PTX and bevacizumab [21][22][23]30]. Using nab-PTX alone, the rates of grade 3-4 leukopenia, neutropenia, and anemia have been reported to be 5%-49%, 2%-69%, and 0%-32% [24,27,28,[37][38][39][40]. In a study of nab-PTX combined with carboplatin, neutropenia, thrombocytopenia, and anemia were observed in 28.0%, 12.0%, and 8.0% of the patients, respectively [41].…”
Section: Discussionsupporting
confidence: 73%
“…The results showed that the ORR and DCR were 26.5% and 82.4%, respectively; the median PFS and OS were 6.0 and 11.0 months, respectively. Previous studies of nab-PTX alone in second or further line treatment of NSCLC reported a PFS of 3.5-6.6 months and an OS of 6.8-15.7 months, with ORRs ranging from 16.1%-35.5% [27,28,[37][38][39][40]. A study of nab-PTX combined with carboplatin reported a PFS of 4.0 months and an OS of 14.0 months [41].…”
Section: Discussionmentioning
confidence: 99%
“…[65]. The positive example of using albumin nanoparticles in antitumor treatment is confirmed by a successful application and FDA approval of Abraxane ® (Celegene Corporation, Summit, NJ, USA) (paclitaxel incorporated in albumin nanoparticles for a metastatic breast cancer, non-small cell lung carcinoma, pancreatic cancer, cervical cancer [66,67,68,69,70]. Albumin based nanoparticles loaded with lapatinib (triple negative breast cancer and HER2-positive breast cancer), gemcitabine (pancreatic cancer), siRNAs (breast and lung cancers), gold nanoparticles for NSCLC, photosensitizers are also being developed [71,72,73,74,75,76,77].…”
Section: Passive Targetingmentioning
confidence: 99%
“…The anti‐cancer agent azacitidine can upregulate the SPARC expression in tumors, and then promote the accumulation of albumin‐bound drugs at tumor site . NAB‐paclitaxel has been reported have convincing antitumor activity for the treatment of advanced NSCLC .…”
Section: Discussionmentioning
confidence: 99%